Leucine-enriched amino acid supplementation and exercise to prevent sarcopenia in patients on hemodialysis: a single-arm pilot study - Ju, Sang-Hyeon; Lee, Eu Jin; Sim, Byeong Chang; Nga, Ha Thi; Lee, Ho Yeop; Tian, Jingwen; Cho, Kyu Jeong; Park, Hyoungsu; Choi, Dae Eun; Ham, Young Rok; Yi, Hyon-Seung (Frontiers in Nutrition, 2023)
Background Sarcopenia, which is strongly associated with mortality and quality of life, occurs in up to 40% of hemodialysis patients. Here, we investigated the preventive effects of leucine-enriched amino acid supplementation and resistance exercise in non-sarcopenic hemodialysis patients, and characterized the biochemical and immunophenotypic profiles of those who benefited from the intervention. Methods Twenty-two patients on maintenance hemodialysis at our hospital were enrolled in this single center, prospective, single-arm pilot trial. For the first 12 weeks, the subjects were administered a total of 6 g of leucine per day. Three grams were supplied via capsules, and the remaining three grams were provided via beverages containing macro- and micro- nutrients, such as 10 μg of vitamin D and 290 mg of calcium. The supplements were not provided for the next 12 weeks. Muscle mass, grip strength, and physical performance were measured using the bioimpedance analyzer (BIA), handgrip strength (HGS), and short physical performance battery (SPPB) protocols, respectively, at baseline, 12 weeks, and 24 weeks. In addition, serum biochemistry, immunophenotype of peripheral blood mononuclear cells, and nutritional status was assessed at the three time points. Those who showed 5% or more improvement in parameters were defined as responders, otherwise, as non-responders (ClinicalTrials.gov identification number: NCT04927208). Results Twenty-one out of twenty-two patients (95.4%) showed improvement in at least one or more parameters among muscle mass, grip strength, and physical performance. After 12 weeks of intervention, skeletal muscle index was increased in 14 patients (63.6%), and grip strength was improved in 7 patients (31.8%). Baseline grip strength lower than 35.0 kg was the strongest predictor of improvement in grip strength (AUC 0.933 from ROC curve). Grip strength showed a significant increase in females than males (7.6 ± 8.2 vs. −1.6 ± 7.2%, p = 0.03), in age over 60 than under 60 (5.3 ± 6.2 vs. −1.4 ± 9.1%, p = 0.04), and in higher (≥95%) than lower (<95%) exercise compliance (6.8 ± 7.7 vs. −3.2 ± 6.4%, p = 0.004). In SPPB study, gait speed and sit-to-stand time was improved in 13 patients (59.1%) and 14 patients (63.6%), respectively. Baseline hemoglobin lower than 10.5 g/dl and hematocrit lower than 30.8% were predictor of improvement in the sit-to-stand time (AUC 0.862 and 0.848, respectively). Serum biochemistry results showed that, compared to non-responders, responders in muscle mass had lower baseline monocyte fraction (8.4 ± 1.9 vs. 6.9 ± 1.1%, p = 0.03), and responders in grip strength had lower baseline total protein (6.7 ± 0.4 vs. 6.4 ± 0.3 g/dL, p = 0.04). Immunophenotypic analysis found that the intervention tended to increase the naïve/memory CD8+ T cell ratio (from 1.2 ± 0.8 to 1.4 ± 1.1, p = 0.07). Conclusion Leucine-enriched amino acid supplementation and resistance exercise induced significant improvement in muscle mass, strength, and physical function in subpopulation of the non-sarcopenic hemodialysis patients. Those who benefited from the intervention were old-age females with lower baseline grip strength or lower hemoglobin or hematocrit, and who have good exercise compliance. Therefore, we propose that the intervention will help to prevent sarcopenia in selected patients on maintenance hemodialysis.